Pemberdayaan Masyarakat Melalui Sosialisasi Pola Gizi Seimbang dan Pencegahan Stunting di Posyandu Tunggul Hitam - Anggun Patricia; Fadillah Aulia; Harpi Ibranaldi; Yulia Hanoselina (CV. ITTC INDONESIA, 2025)
Stunting is one of the public health problems that is still a serious concern in Indonesia, especially in rural areas. This condition occurs due to chronic malnutrition over a long period of time, especially during the First 1,000 Days of Life (HPK), which has a negative impact on physical growth, cognitive development, and the level of intelligence and productivity of children in the future. Stunting also increases the risk of chronic diseases, thus becoming an obstacle in realizing a healthy and productive generation. Based on WHO data, Indonesia ranks third highest in the prevalence of stunting in toddlers in the Southeast Asia region. Therefore, real intervention is needed through a community empowerment approach. This community service activity was carried out at the Tunggul Hitam Integrated Health Post through socialization of balanced nutrition patterns and stunting prevention targeting mothers who have babies and toddlers. This socialization is part of a community empowerment effort that aims to increase awareness, knowledge, and behavioral changes in maintaining family health and nutrition. The material presented includes an understanding of balanced nutritious food, the importance of exclusive breastfeeding, environmental sanitation, and proper parenting patterns. The results of the activity showed an increase in participants' understanding of the importance of balanced nutrition and efforts to prevent stunting. In general, socialization has a positive impact in encouraging healthy living behavior among the community, especially mothers as the main decision makers in child care. This activity not only provides short-term benefits in the form of increased awareness, but also opens up opportunities for the development of similar programs in other regions as part of the national strategy to reduce stunting rates.